Desarrollo de un sistema para el monitoreo de recursos hídricos en el hogar - Fonseca-Revelo, Jorge-Esteban; Fonseca-Revelo, Juan-Camilo; Cerón-Correa, Alexander (Revista Científica, 2024)
The efficient management of natural resources such as water is necessary to ensure an optimized use. Water is an indispensable resource for life, and it is at risk of becoming scarce. Although public utility companies provide information about a household’s consumption, it is insufficient to identify and prevent each person’s excessive consumption. Therefore, the main objective of this article is to propose a household water consumption monitoring system using flow sensors and to present it to the user in a friendly and efficient manner by means of an app based on the advances of the Internet of Things. The collected information, presented in a format that is easy to understand, is a clarifying resource for users and allows them to make informed decisions and take measures aimed at reducing their environmental footprint.